An environmental magnetism approach to assess impacts of land-derived sediment disturbances on coral reef ecosystems (Cartagena, Colombia) - Mejia Echeverry, Daniela (2018)
We used environmental magnetism methods to study recently deposited marine sediments from the estuarine ecosystems on the Caribbean coast of Colombia. Cartagena region has undergone an increasing sediment load during the last decades via sediment plumes from Magdalena River and its distributary man-made channel. Concentration dependent magnetic parameters show an increasing abundance of ferrimagnetic minerals on the uppermost sediments on sites located close to the continent (remanent magnetization SIRM = 5.4-9.5 × 10−3Am2 kg−1) as well as faraway sites (SIRM = 0.5-1.7 × 10−3Am2 kg−1 near Rosario Islands coral reef complex). The magnetic grain size and mineralogy along the cores are variable, showing the dominance of the magnetite-like minerals (remanent coercivity Hcr = 34.3-45.3 mT), with a minor contribution of high-coercivity minerals (Hcr = 472-588 mT). In addition, there is a moderate enrichment of elements Cu, Mo, and Zn (enrichment factor EF = 1.5-3.8) that indicates the additional land-derived contribution on sediments. The environmental magnetism approach, which shows significant signals of magnetic minerals and trace elements, is a reliable tool to prove the presence of continental sediment supply in coral reef ecosystems.